Bioinspired fabrication of CuONPs synthesized via Cotoneaster and application in dye removal: antioxidant and antibacterial studies - Isiksel, Ecem; Attar, Azade; Mutlu, Ozge; Yapaoz, Melda Altikatoglu (SPRINGER HEIDELBERG, 2023)
In this study, bioinspired fabrication of copper oxide nanoparticles (CuONPs) which are widely researched in nanotechnology field with Cotoneaster extract was performed. Cotoneaster plant extract was chosen as a good antioxidant and antibacterial agent in terms of the amount of phenolic and flavonoid compounds it contains. The obtained CuONPs were characterized by UV-Vis, FTIR, and SEM analyses. Antibacterial activity of the fabricated nanoparticles was evaluated against Escherichia coli and Staphylococcus aureus. Total phenolic compound, total flavonoid amount, and reducing power of the CuONPs were determined. Furthermore, paint removal properties of copper oxide nanoparticles on various dyes were investigated. Fabrication of the CuONPs was evaluated morphologically by color change and in UV spectrum by SPR band at 338 nm. The characteristic peak of CuONPs at 621 cm(-1) was monitored employing FT-IR. SEM results showed that the fabricated CuONPs were spherical and between 50 and 160 nm. The CuONPs represented notable antibacterial efficiency against E. coli and S. aureus with inhibition zone of 19 +/- 1 and 23 +/- 2, respectively employing disk diffusion. The antioxidant properties of the CuONPs were also confirmed. Total phenolic substance content of the CuONP solution was 6.04 mu g pyrocathecol equivalent/mg nanoparticle and total flavonoid content value was found as 122.46 mu g catechin equivalent/mg nanoparticle. The reducing power of the fabricated CuONPs was found to be good when compared to the standard antioxidants BHA and alpha-tocopherol. In addition, the decolorization efficiency of the fabricated CuONPs has a strong potential on the industrial dye removal of neutral red and naphthol blue black.
Keywords: Copper oxide nanoparticles; Cotoneaster; Bioinspired fabrication; Antibacterial activity; Dye removal; COPPER-OXIDE NANOPARTICLES; GREEN SYNTHESIS; SILVER NANOPARTICLES; EXTRACT; FOOD; Environmental Sciences & Ecology